Hydrogeological Modelling of Geothermal Waters in Yenice (Buldan, Denizli) and Environs, Turkey. Issue 1 (December 2020) - Özgür, Nevzat; Aslan, Cihan
Abstract: The study deals with hydrogeological modelling of geothermal waters in Yenice located in the southern margin of the continental rift zone of the Büyük Menderes where it incorporates with the rift zone of the Gediz within the Menderes Massif in which hydrogeological, hydrogeochemical andi sotope geochemical methods were used. In Yenice and environs, Paleozoic metamorphic rocks forms the basement overlain by Neogene sedimentary rocks such as Kızılburun formation, Sazak formation, Kolonkaya formation and Tosunlar formation. These rocks are overlain by Quaternary alluviums and travertine deposits. Geothermal waters in the area of Yenice are of meteoric origin and show intense water-rock interaction. These geothermal waters can be considered as Ca-Na-(SO4 )-HCO3 type. Moreover, geothermal waters have an order of cations of Na+K>Ca>Mg and anions of HCO3 >SO4 >Cl. Geothermal waters of the study area are distinguished by surface temperatures from 36 to 70 °C, pH values between 6 and 6.85 and electrical conductivity values ranging from 1950 to 5000 µS/cm. According to calculations of geochemical thermometers, geothermal waters of Yenice show reservoir temperatures between 170 and 230 °C and can be classified as immature waters.